2020
DOI: 10.35848/1347-4065/aba456
|View full text |Cite
|
Sign up to set email alerts
|

Atomic nitrogen density measurements by actinometry method in the toroidal device NAGDIS-T

Abstract: Nitrogen (N) atomic density is measured by an actinometry method in the toroidal shaped plasma device NAGDIS-T, where the plasma produced in a DC arc discharge is cooled as spiraling down inside the vacuum vessel. The plasma was characterized with an electrostatic probe, and we applied the actinometry method to obtain the N density using the deduced electron density and temperature. The actinometry method used the Ar line emissions at 750.4 or 811.5 nm and N emission at 746.8 nm. The measured N densities from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…At p n = 4.74 mTorr and I d = 10 A, n N reached 6.2 × 10 17 m −3 . The actinometry resulted in nearly consistent values with the VUVAS and it decreases with p n [6].…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…At p n = 4.74 mTorr and I d = 10 A, n N reached 6.2 × 10 17 m −3 . The actinometry resulted in nearly consistent values with the VUVAS and it decreases with p n [6].…”
mentioning
confidence: 56%
“…In previous studies using the NAGDIS-T, n N in the ground state was measured spectroscopically by assuming coronal equilibrium [5] and by actinometry [6]. As a result, it was confirmed that n N was on the order of 10 17 m −3 .…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The density can then be determined because it is proportional to the ratio of the above lines, due to the population of the excited states being assumed to have been excited from the ground state. Some studies used this traditional actinometry method to obtain the densities of N, O, and F atoms [22][23][24][25][26]. However, the assumption that excitation from the ground state dominates the population of the measured states is incorrect in some operating conditions.…”
Section: Introductionmentioning
confidence: 99%